"LOOK FOR NAME IN SERVICE” STUDY HERMENEUTICS CRITICISM HISTORICAL INCIDENT 11 : 1- 9 - Gracella Walukow (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
This article discusses humans who seek a name for their own fame in Genesis 11:1-9. Those humans want to find a name so that they will not be scattered all over the earth. The construction of the tower of Babel became a popular story in the days of Noah's descendants because of its towering structure. This became a reference for the humans to seek a name so that the whole world would recognize their greatness and power. The Tower of Babel became a symbol of human pride and arrogance. Seeking a name outside of God is inappropriate and will only bring the Lord's wrath, instead the right thing to do is for man to approach the LORD God not to seek a name for his greatness but to glorify the LORD. Therefore, in relation to this point, the research was conducted through hermeneutic work with the method of historical criticism. The researcher does hermeneutic work to get the right meaning and can be a reference for readers, especially for the GMIM Alfa Omega Kumaraka In .